Peran Organisasi Santri dalam Pembentukan Karakter Disiplin Sholat Jamaah di Pondok Pesantren Jabal Noer Sidoarjo - Azizah, Imroatul; Chabib Musthofa (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2024)
This research aims to explore the role of the Jabal Noer Santri Organization (OSJN) in forming the disciplined character of congregational prayer at the Jabal Noer Islamic Boarding School, Sidoarjo. Character education, especially discipline, is a crucial element in the educational process, which has undergone various changes since Indonesia's independence until now. Descriptive qualitative research methods were used to analyze the role of OSJN, with data collection techniques including interviews, observation and documentation. Primary data was obtained through interviews with OSJN supervisors and board members as well as students, while secondary data was collected from related academic references. The findings show that OSJN is significant in increasing the discipline, responsibility and religiosity of students through an organizational structure that supports the consistent implementation of worship. OSJN functions to form student discipline in carrying out congregational prayers by arranging worship schedules and providing social control mechanisms. Developing student responsibility and leadership, as well as strengthening religiosity through structured worship routines. With effective coaching, OSJN supports the formation of better character for students, both in spiritual and social aspects. This research concludes that OSJN has an important role in forming the disciplined character of congregational prayer and requires continuous efforts to increase its effectiveness. OSJN's success in developing the character of students reflects the importance of organizational structure and the integrity of religious activities in character education in Islamic boarding schools.